Automobility of Novice Drivers in Iceland: Socialities, Individuation and Spacings - Collin-Lange, Virgile , 1983- (2013)
This Ph.D. thesis explores the automobility of Icelandic novice drivers from a geographical point of view. Automobility, its system and its regime, has recently been subject to intense discussions among scientists in different fields, ranging from sociology to urban studies. The debates have focused on the importance of cars in current societies, gender issues related to car use, or simply the amount of space dedicated to cars in cities. This thesis will address in particular how young people enter the systemic regime of automobility and how this entry reflects how the system perpetuates itself. In terms of automobility, Iceland is an interesting case, as it is one of the countries in the world with one of the highest rates of car ownership per capita. Car use in Iceland is extensive and young people are not an exception. The high level of car use ties in with a previous planning decision: the transport system of the Capital area of Iceland has been shaped almost exclusively for and by cars. Yet, there are further reasons. In examining the case of Icelandic young drivers, this thesis explores current and potential theoretical ventures in automobility. It explores the social and cultural structuring upon which the local systemic regime of automobility in Iceland hinges. It first presents the results of a survey submitted to young drivers in Iceland and analyses their responses. The results of the survey show that young people in Iceland use cars extensively. Second, it explores in detail a particular activity – car cruising, or rúntur in Icelandic – which has particular cultural and social significance for young drivers in Iceland. By looking at the rúntur, the thesis also analyses how young peoples’ participation in car cruising allows individuals to integrate themselves in and cope with the systemic regime of automobility in Iceland, thus elucidating some of the cultural and social elements behind their high level of car ownership and use. Í þessari doktorsritgerð er þýðing einkabílsins meðal ungra íslenskra ...